Kesiapan Menikah Pada Wanita Berpendidikan S2 (Studi Kasus Pada Mahasiswi S2 Psikologi) - sri nurgroho jati (Universitas Muhammadiyah Pontianak, 2013)
Readiness married a ready state, ready to accept responsibility as a husband or wife, ready to intercourse, ready set and ready family child care. Women receive greater pressure to get married than men after a certain age, usually around the age of 30 years. This research is a case study which aims to describe the dynamics of readiness to marry educated women S2. The sample in this study is three (3) subjects with backgrounds are studying Psychology and S2 are female. The results of the study showed no similarity in all three subjects in readiness to marry, namely: tolerance, willing intimate relationships, affection and willing to share with others. These three themes have in common a high intensity. Background owned by each of the three subjects with the pair making the subject has an emotional maturity level is different.